2020 IEEE Sixth International Conference on Multimedia Big Data (BigMM) 2020
DOI: 10.1109/bigmm50055.2020.00062
|View full text |Cite
|
Sign up to set email alerts
|

Spread & Peak Prediction of Covid-19 using ANN and Regression (Workshop Paper)

Abstract: , caused by Severe Acute Respiratory Syndrome Coronavirus 2 (SARS-CoV-2) virus, has presented tough times for countries all over the world with number of cases and casualties running in millions. While virologists and doctors have spent sleepless nights to come up with a potent vaccine, the work life of government personnel including administrative staffs, hospital employees etc. has not been any easier. Amidst this turmoil, the common question crossing every mind is concerned with the statistics about this in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 21 publications
0
11
0
Order By: Relevance
“…Various studies related to virus transmission and its influence factors have been carried out to predict (a) the spread of the virus [29,30,31,32,33]; (b) the person suspected of being infected [34]; (c) new infection areas [35]; (d) the likelihood of the second and third waves of the epidemic [36]; (e) COVID-19 contamination scenario based on people movement [37]; and (f) the increased number of cases [38]. COVID-19 task-force stakeholders can use these epidemiological predictions to prepare the necessary measures and policies.…”
Section: Healthcarementioning
confidence: 99%
See 1 more Smart Citation
“…Various studies related to virus transmission and its influence factors have been carried out to predict (a) the spread of the virus [29,30,31,32,33]; (b) the person suspected of being infected [34]; (c) new infection areas [35]; (d) the likelihood of the second and third waves of the epidemic [36]; (e) COVID-19 contamination scenario based on people movement [37]; and (f) the increased number of cases [38]. COVID-19 task-force stakeholders can use these epidemiological predictions to prepare the necessary measures and policies.…”
Section: Healthcarementioning
confidence: 99%
“…This technique predicts future events by analyzing past trends, assuming that future trends will be similar to historical trends. A study on COVID-19 has applied a regression model to predict infected cases and compared the model with another prediction model of ANN [31]. ANN is also used to indicate the spread and the peak number of COVID-19 cases.…”
Section: Regression and Time Series Forecastingmentioning
confidence: 99%
“…The same authors used the logistic model to forecast daily predictions and the epidemic size for China, South Korea, and the rest of the World [12]. Prakash [26] used ANN and regression to model the COVID-19 pandemic in India and other countries like The USA, Italy and Spain. The authors observed that the results of polynomial regression follow the ground truths in India and the USA but not in Italy and Spain.…”
Section: Introductionmentioning
confidence: 99%
“…Prakash [26] used ANN and regression to model the COVID-19 pandemic in India and other countries like The USA, Italy and Spain. The authors observed that the results of polynomial regression follow the ground truths in India and the USA but not in Italy and Spain.…”
Section: Introductionmentioning
confidence: 99%
“…[ [17] considered a new model algorithm, which replaced the regression [18] with the regression to improve the performance of the approach. Thus, [2] proposed another predictive models where some potential predictor variables are considered.…”
Section: Introductionmentioning
confidence: 99%